Factores psicosociales durante el confinamiento por el Covid-19 – Perú - Apaza P., Cynthia M.; Seminario Sanz, Roberto Simón; Santa-Cruz Arévalo, Johanna Elena (Revista Venezolana de Gerencia, 2020)
.